Procedure for Handling 4-H Accounts: Audits - Marilyn N. Norman; Joy C. Jordan (EDIS)
4H5.4, a 3-page factsheet by Marilyn N. Norman and Joy C. Jordan, reviews the procedures for the annual audit required of all 4-H units. Published by the UF Department of Family, Youth and Community Sciences, February 2007.